Problems, Effects, and Methods of Monitoring and Sensing Oil Pollution in Water: A Review - Nur Nazifa Che Samsuria; Wan Zakiah Wan Ismail; Muhammad Nurullah Waliyullah Mohamed Nazli; Nor Azlina Ab Aziz; Anith Khairunnisa Ghazali (MDPI AG, 2026)
Indexed by WOS/ Scopus